2009
DOI: 10.1055/s-0029-1237701
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Elastography and Contrast-Enhanced Ultrasound for the Assessment of Thyroid Nodules

Abstract: RTE seems to be a useful tool in the work-up of thyroid nodules to exclude papillary thyroid cancer. However, follicular carcinoma remains a challenging problem. CEUS did not improve the characterization of thyroid nodules in this preliminary study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
83
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 15 publications
4
83
1
5
Order By: Relevance
“…[18][19][20][21] Recent studies have evaluated the use of US elastography for detecting malignant thyroid nodules. [23][24][25][26][27][28][29][30][31][32] These uniformly suggest that US elastography increases the ability to discriminate benign and malignant nodules. Recently, Bojunga et al 31 published a meta-analysis of elastography for the differentiation of benign and malignant thyroid nodules, concluding that US elastography can be used with high sensitivity in the work-up of thyroid nodules and might be a useful method in addition to or even instead of FNAB to select patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20][21] Recent studies have evaluated the use of US elastography for detecting malignant thyroid nodules. [23][24][25][26][27][28][29][30][31][32] These uniformly suggest that US elastography increases the ability to discriminate benign and malignant nodules. Recently, Bojunga et al 31 published a meta-analysis of elastography for the differentiation of benign and malignant thyroid nodules, concluding that US elastography can be used with high sensitivity in the work-up of thyroid nodules and might be a useful method in addition to or even instead of FNAB to select patients for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most publications referring to US elastography in the evaluation of thyroid nodules propose a scale of tissue stiffness based on the color of the elastograms: 4-point scales, [23][24][25][26] 5-point scales, 28 and 6-point scales. 24 Lyshchik et al 26 evaluated 52 thyroid nodules in 31 patients and found a specificity of 96% and a sensitivity of 82%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no statement on the diagnostic accuracy of SE for follicular carcinoma can be made. Previous studies have reported that both FNA and SE have difficulties in the diagnosis of follicular carcinoma [3, 16,27,38,46]. In a meta-analysis on SE including 8 studies, 44 % of follicular carcinoma were not detected as malignant thyroid nodules using SE.…”
mentioning
confidence: 97%
“…TIC parameters of shape have been assessed by Ferrari et al, 2008;Nemec et al, 2012and Giusti et al, 2013. Ferrari et al (2008 found that in malignant thyroid nodules wash-in and peak-enhancement occurred significantly faster than in benign mass lesions, whereas Nemec et al (2012), Friedrich-Rust et al (2010, and Giusti et al (2013) did not find a significant difference between the malign and benign nodules. In the Nemec's study, the relative intensity of the contrast enhancement was calculated rating the maximum enhancement against the base enhancement, with 84.4% sensitivity, 76.9% specificity and 82.6% diagnostic accuracy (Nemec et al, 2012).…”
Section: Discussionmentioning
confidence: 99%